THE INFLUENCE OF THE ALKALINE EARTH CATIONS, MAGNESIUM, CALCIUM, AND BARIUM ON THE DISSOLUTION KINETICS OF QUARTZ - Dove P.M.; Nix C.J. (My University, 1997)
This study quantifies the influence of the four major dissolved solutes found in terrestrial and marine environments on the dissolution kinetics of quartz. Dissolution rates are dependent upon the concentration and identity of alkali and alkaline earth cations in near-neutral pH solutions. We determine the effect of alkaline earth cations upon quartz reactivity by measuring dissolution rates in 0.0001-0.2 molal solutions of MgCl2, CaCl2, BaCl2, LiCl, KCl, and NaCl at near-neutral pH and 200°C. The results fit a first order rate law, where dissolution rates are slowest in pure water and increase with the introduction of salts in the order: Mg2+ < Ca2+ # Li+ # Na+ # K+ < Ba2+. The trend is consistent with previously reported lower temperature measurements of dissolution rate for amorphous silica and sources of quartz. This suggests cation-specific effects hold for multiple silica polymorphs over temperatures of 25-200°C.Combining evidence from the literature and the kinetic data presented in this study, we propose a simple model: The dissolution rate of quartz. Alkali and alkaline earth cations indirectly enhance dissolution by modifying rates of solvent motion, exchange, or orientation at the mineral-solution interface. Rate enhancement is proportional to the concentration of ions at the surface and their solvation character. The resulting model predicts (1) the dissolution rate of quartz for a suite of cations with weak surface interactions, (2) the influence of ion concentration, (3) that the catalyzing effect of salts diminish as the concentration of silicic acid in solution increases (decreasing reaction affinity) by increasing the amount of H4SiO4 at the interface, (4) that electrolytes have little rate-enhancing effect on the dissolution kinetics of silicate minerals, and (5) that dissolution rates of other oxide materials containing constituents with sluggish solvent interactions are also enhanced by introduction of alkali or alkali cations. Our findings reiterate the need to understand relationships between near-surface solute/solvent properties and mineral reactivity.